In2O3 microcrystals obtained from rapid calcination in domestic microwave oven - Motta, F. V. [UNESP]; Lima, R. C.; Marques, A. P. A.; Leite, E. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
The simple way to prepare In2O3 microcrystals is reported in this paper. The precursor, In(OH)(3) microstructures, were obtained using the Microwave-Assisted Hydrothermal (MAH) Method. By annealing as-prepared In(OH)(3) precursor at 500 degrees C for 5 min in a domestic microwave oven (MO), In2O3 microcrystals were prepared, inheriting the morphology of their precursor while still slightly distorted and collapsed due to the In(OH)(3) dehydration process which was studied by thermal analysis. The In(OH)(3) and In2O3 were characterized using powder X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM) and Raman spectroscopy. These techniques confirm the chemical dehydration of In(OH)(3) and the formation of In2O3 powders. The domestic MO promotes a rapid structural organization as compared with a CF (conventional furnace). The MAH method and the subsequent annealing in a domestic MO were shown to be a low cost route for the production of In2O3, with the advantages of lower temperature and smaller time. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Oxides; Semiconductors; Chemical synthesis; Electron microscopy